2021
DOI: 10.1186/s12964-021-00735-w
|View full text |Cite|
|
Sign up to set email alerts
|

Hyoscyamus albus nortropane alkaloids reduce hyperglycemia and hyperinsulinemia induced in HepG2 cells through the regulation of SIRT1/NF-kB/JNK pathway

Abstract: Background Chronic superphysiological glucose and insulin concentrations are known to trigger several tissue and organ failures, including insulin resistance, oxidative stress and chronic low-grade inflammation. Hence, the screening for molecules that may counteract such conditions is essential in current existing therapeutic strategies, thereby the use of medicinal plant derivatives represents a promising axis in this regard. Methods In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Exercise training caused a significant decrease in activity in the kidney, though no significant change was observed in the liver. Activation of the PI3K/Akt/Glut-4 pathway has been known to be significantly involved in the regulation of insulin signaling and glucose metabolism and defects in the insulin signaling pathway, which lead to glucose homeostasis could lead to insulin resistance ( Marinho et al, 2014 ; Rai et al, 2019 ; Kowalczuk et al, 2021 ; John et al, 2022 ). Our current study also showed activation of Akt and improved expression of Glut-4 protein after exercising, implying improved glucose homeostasis and increased insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training caused a significant decrease in activity in the kidney, though no significant change was observed in the liver. Activation of the PI3K/Akt/Glut-4 pathway has been known to be significantly involved in the regulation of insulin signaling and glucose metabolism and defects in the insulin signaling pathway, which lead to glucose homeostasis could lead to insulin resistance ( Marinho et al, 2014 ; Rai et al, 2019 ; Kowalczuk et al, 2021 ; John et al, 2022 ). Our current study also showed activation of Akt and improved expression of Glut-4 protein after exercising, implying improved glucose homeostasis and increased insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Akt, a downstream target of PI3K, is triggered by the activation of insulin receptor in insulin signal pathway and facilitates the uptake of glucose with GLUT. Besides, the increased PI3K activity and activated Akt also can increase the insulin-stimulated glucose disposal [7]. Therefore, stopping JNK/PI3K/Akt pathway is an approach of stopping oxidative and in ammatory insult at the initiation of IR and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JNK, as the common point of oxidative stress and in ammation, its phosphorylation can trigger the serine phosphorylation of IRS-1 and lead to IR. These series of reports clearly provide evidence that ROS and in ammatory factors can phosphorylate JNK [7], and controlling JNK may play an indispensable role in preventing IR [8]. Taken all of these together, alleviating oxidative stress and in ammation may be e cient and reliable in preventing IR and T2DM.…”
Section: Bcakgroundmentioning
confidence: 99%
“…Hyperglycemia can trigger oxidative stress and promote the production of pro-inflammatory factors, such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), which can result in the activation of the NF-kB pathway and further promote the synthesis of inflammatory factors, disrupting diabetic wound healing [ 69 ]. Fan et al showed that HBMMSCS-derived exosomes (HBMMSCS-exos) significantly inhibited the expression of pro-apoptotic proteins and pro-inflammatory factors, while the expression of anti-apoptotic proteins and anti-inflammatory factors was up-regulated in lipopolysaccharide (LPS)-induced PC12 cell apoptosis [ 70 ].…”
Section: The Signaling Pathways Of Exosomes In Promoting Diabetic Wou...mentioning
confidence: 99%